Teachers' Challenges to Conduct Assessment in Elementary Schools Using Merdeka Curriculum - Kumalasari, Diva; Mukaromah, Dyah (Jurnal Bahasa Inggris Terapan, 2024)
As a result of the Merdeka curriculum modification, teachers are confronting new challenges. This curriculum encourages students to be more active and to have products in their skills, which might put pressure on instructors when it comes to completing assessments. To encounter this matter, English teachers especially at the elementary school level employ a range of strategies with students in order to stimulate their interest and reduce monotony in English studies. These approaches are meant to assist students and teachers in meeting assessment objectives. They are responsible for providing a favorable learning environment that not only engages students but also helps them enhance their skills. This research will also look into the effectiveness of different teaching styles in reaching the new curriculum's objectives. It is envisaged that the outcomes of this study would be useful for instructors negotiating the transition to the Merdeka curriculum. The goal of this study is to examine the issues that instructors face and how they deal with them. Teachers must be imaginative and adaptable in their teaching approaches in order to meet these challenges.